Frogs and Toads of the Tallgrass Prairie - Joseph T. Collins (Symphony in the Flint Hills, 2011)
About a hundred species of frogs and toads are found on the North American continent north of Mexico, providing a diversity of seasonal calls that are fascinating to most people but often difficult to sort out.
Keywords: Frogs; todas; tallgrass; prairie; diveristy; species; North America; amphibians; pond; Silent Spring; chorus; anurans